2014
DOI: 10.3109/08880018.2014.949941
|View full text |Cite
|
Sign up to set email alerts
|

herg1bExpression as a Potential Specific Marker in Pediatric Acute Myeloid Leukemia Patients with HERG 897K/K Genotype

Abstract: Human ether-a-go-go related gene (herg) encoding HERG K(+) channel has been demonstrated in many previous studies with its association to cell cycle progression and growth in tumor cells. The upregulated expression of HERG K+ channels was determined in different tumor types. Furthermore, not only full-length transcript herg1 but also a truncated isoform herg1b was shown to be expressed in cancer cells. In this study, the expression levels of herg1 and herg1b and the impact of K897T mutation on their expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“…Finally, the truncated, N-deleted splice variant hERG1b is reportedly up-regulated during the S phase of cell cycle, while the full-length hERG1a protein increases its expression on the plasma membrane during the G1 phase (Crociani et al, 2003). Consequently, proliferating tumor cells should exhibit higher hERG1b/1a expression ratios than terminally differentiated cardiomyocytes (Larsen et al, 2008) as has indeed been reported for some tumors (Erdem et al, 2015). Inhibitor selectivity for variant 1b over 1a (Gasparoli et al, 2015) might be a further strategy to develop tumor-specific hERG1 blockers.…”
Section: Discussionmentioning
confidence: 60%
“…Finally, the truncated, N-deleted splice variant hERG1b is reportedly up-regulated during the S phase of cell cycle, while the full-length hERG1a protein increases its expression on the plasma membrane during the G1 phase (Crociani et al, 2003). Consequently, proliferating tumor cells should exhibit higher hERG1b/1a expression ratios than terminally differentiated cardiomyocytes (Larsen et al, 2008) as has indeed been reported for some tumors (Erdem et al, 2015). Inhibitor selectivity for variant 1b over 1a (Gasparoli et al, 2015) might be a further strategy to develop tumor-specific hERG1 blockers.…”
Section: Discussionmentioning
confidence: 60%
“…Wang et al later reported that the hERG channel is a regulator of tumour cell proliferation and apoptosis. This channel is also overexpressed in leukaemia cells, regulating their proliferation . Using immunohistochemistry and real‐time PCR techniques, Liang et al have shown that the expression rate of hERG in laryngeal carcinomatous tissue was far higher than in mucosa adjacent to the cancer.…”
Section: Resultsmentioning
confidence: 99%
“…hERG1 is a voltage-dependent potassium channel, the functional relevance of which in human leukemia has been repeatedly proven (7,(9)(10)(11). Furthermore, the alternative transcript of the hERG1 gene, hERG1B, is an independent prognostic factor of a high risk of relapse in pediatric T-ALL (12).…”
Section: Introductionmentioning
confidence: 99%